Angiotensin AT2 Receptor Stimulation Alleviates Collagen-Induced Arthritis by Upregulation of Regulatory T Cell Numbers - Sehnert, Bettina; Valero-Esquitino, Veronica; Schett, Georg; Unger, Thomas; Steckelings, Ulrike Muscha; Voll, Reinhard Edmund (Frontiers in Immunology, 2022)
The angiotensin AT2 receptor (AT2R) is a main receptor of the protective arm of the renin-angiotensin system and exerts for instance anti-inflammatory effects. The impact of AT2R stimulation on autoimmune diseases such as rheumatoid arthritis (RA) is not yet known. We investigated the therapeutic potential of AT2R-stimulation with the selective non-peptide AT2R agonist Compound 21 (C21) in collagen-induced arthritis (CIA), an animal model for inflammatory arthritis. Arthritis was induced by immunization of DBA/1J mice with collagen type II (CII). Prophylactic and therapeutic C21 treatment alleviates arthritis severity and incidence in CIA. Joint histology revealed significantly less infiltrates of IL-1 beta and IL-17A expressing cells and a well-preserved articular cartilage in C21- treated mice. In CIA, the number of CD4+CD25+FoxP3+ regulatory T (Treg) cells significantly increased upon C21 treatment compared to vehicle. T cell differentiation experiments demonstrated increased expression of FoxP3 mRNA, whereas IL-17A, STAT3 and IFN-gamma mRNA expression were reduced upon C21 treatment. In accordance with the mRNA data, C21 upregulated the percentage of CD4+FoxP3+ cells in Treg polarizing cultures compared to medium-treated controls, whereas the percentage of CD4+IL-17A+ and CD4+IFN-gamma+ T cells was suppressed. To conclude, C21 exerts beneficial effects on T cell-mediated experimental arthritis. We found that C21-induced AT2R-stimulation promotes the expansion of CD4+ regulatory T cells and suppresses IL-17A production. Thus, AT2R-stimulation may represent an attractive treatment strategy for arthritis.